Community ophthalmology: from darkness to light “There is no better way to thank God for your sight than by giving a helping hand for someone in dark.” - Nahata, Manak (Nepalese Journal of Ophthalmology, 2016)
Community ophthalmology deals with all aspects of vision covering a wide range of fields for work – Prevention of blindness, conservation of sight, social service, promotion of employment, rehabilitation and recreation of the blind. Community ophthalmology is attracting the attention of ophthalmic world. This delivery of eye care involves preventive, curative, promotive and rehabilitative activities incorporating basic clinical and public health sciences in all its dimensions. It highlights the realignment from individualized care to community based eye care services. Community ophthalmology is seen as a health management approach in preventing eye diseases, lowering eye morbidity or eye morbidity rates and promoting eye health through active community participation at the ground level. Comprehensive eye care services must start where people live and work and such is the thrust of community ophthalmology. Prevention and promotion should begin amongst the people. Nepal J Ophthalmol 2016; 8(15): 3-9